Anticancer Evaluation of Methoxy Poly(Ethylene Glycol)-b-Poly(Caprolactone) Polymeric Micelles Encapsulating Fenbendazole and Rapamycin in Ovarian Cancer - Shin YB; Choi JY; Shin DH; Lee JW (International Journal of Nanomedicine, 2023)
Yu Been Shin,1,* Ju-Yeon Choi,2,* Dae Hwan Shin,1 Jeong-Won Lee2,3 1College of Pharmacy, Chungbuk National University, Cheongju, 28160, Republic of Korea; 2Research Institute for Future Medicine, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, South Korea; 3Department of Obstetrics and Gynecology, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, South Korea*These authors contributed equally to this workCorrespondence: Dae Hwan Shin, College of Pharmacy, Chungbuk National University, Osongsaengmyeong 1-ro, Osong-eup, Heungdeok-gu, Cheongju, 28160, Republic of Korea, Tel +82 43 261 2820, Fax +82 43 268 2732, Email dshin@chungbuk.ac.kr Jeong-Won Lee, Department of Obstetrics and Gynecology, Samsung Medical Center, Sungkyunkwan University School of Medicine, 81, Irwon-ro, Gangnam-gu, Seoul, 06351, South Korea, Tel +82-2-3410-1382, Fax +82-2-3410-0630, Email garden.lee@samsung.comPurpose: We aimed to inhibit ovarian cancer (OC) development by interfering with microtubule polymerization and inhibiting mTOR signaling. To achieve this, previously developed micelles containing fenbendazole and rapamycin were applied.Methods: Herein, we prepared micelles for drug delivery using fenbendazole and rapamycin at a 1:2 molar ratio and methoxy poly(ethylene glycol)-b-poly(caprolactone)(mPEG-b-PCL) via freeze-drying. We revealed their long-term storage capacity of up to 120 days. Furthermore, a cytotoxicity test was performed on the OC cell line HeyA8, and an orthotopic model was established for evaluating in vivo antitumor efficacy.Results: Fenbendazole/rapamycin-loaded mPEG-b-PCL micelle (M-FR) had an average particle size of 37.2 ± 1.10 nm, a zeta potential of − 0.07 ± 0.09 mV, and a polydispersity index of 0.20 ± 0.02. Additionally, the average encapsulation efficiency of fenbendazole was 75.7 ± 4.61% and that of rapamycin was 98.0 ± 1.97%. In the clonogenic assay, M-FR was 6.9 times more effective than that free fenbendazole/rapamycin. The in vitro drug release profile showed slower release in the combination formulation than in the single formulation.Conclusion: There was no toxicity, and tumor growth was suppressed substantially by our formulation compared with that seen with the control. The findings of our study lay a foundation for using fenbendazole and rapamycin for OC treatment.Keywords: ovarian cancer treatment, combination therapy, drug delivery, nanoformulation